Pusa Sub-District Office / Nurul Farhana Chek Usup - Chek Usup, Nurul Farhana (University Technology MARA Sarawak, 2015)
Pusa is a town in Betong Division Sarawak, east Malaysia. It is situated nearby Saratok town. Mostly form for native Malay for fish village and famous of fish of "ikan terubok" (Toli shad) and also famous for "gula apong" (palm sugar). The water transportation such as of express boats, speed boat and fare boat still become the major transportation for the people in Pusa village. Pusa District is divided into location which is the Pusa village is included Kampung Hulu, Kampung Tengah, Kampung Hilir Pusa, kampung Kalok, Kampung Dato’ Godam, Kampung Lot (Dang Esah), Kampung Hulu, Tengah Hilir Tambak, Kampung Hulu Tengah Hilir Serabang, Pasar Pusa and Kampung Beladin1.